A Non-cooperative Equilibrium for Supergames - Friedman, James W. (Review of Economic Studies, 1971)
Journal Article A Non-cooperative Equilibrium for Supergames Get access James W. Friedman James W. Friedman University of Rochester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 1, January 1971, Pages 1–12, https://doi.org/10.2307/2296617 Published: 01 January 1971